Legal support for integration of renewable energy sources in the energy law of the countries from the international legal position - Ivan A. Kapitonov (Kuwait Journal of Science)
The development of renewable energy sources contributes to energy and environmental security, preservation of the environment, the conquest of world markets for renewable energy sources, conservation of own energy resources for future generations, and increased consumption of raw materials for non-energy use of fuel. Therefore, the topic is popular and deserves attention. The main goal of the work is to analyze the legal support for the integration of renewable energy sources in the energy law of countries with an international legal position. The bases of renewable energy sources’ regulation, namely their structural composition, component basis, regulation principles are studied in the article. The used methods of analysis, comparison, reasoning, description, gave the opportunity to consider the problems in detail. An understanding of alternative and renewable energy, which in the world are generally considered synonymous was established as a result. It is shown that in the framework of regulating the use and development of renewable energy sources, different countries rely on world trends and form the possibility of stratifying the use of the energy sources being researched taking into account the national potential. The results of the research can be used in decisions on the use of renewable sources for municipal, regional and republican authorities, in order to eliminate the energy imbalance and subsequently increase the basis for the development of economic sectors.